Comparative study of the effects of three tunneling methods on ground movements in stiff clay. (April 2018) - Ieronymaki, Evangelia; Whittle, Andrew J.; Einstein, Herbert H.
Abstract: This paper interprets ground movements induced by tunnel construction, by comparing monitoring data with analytical and numerical predictions based on an assumed set of deformation parameters at the cavity boundary. By minimizing differences between the computed and measured ground movements, optimal cavity deformation parameters can then be used to characterize the performance of the tunneling process. We compare the performance of three tunnel construction methods in stiff clay: (i) closed-face excavation using an Earth Pressure Balance (EPB) tunnel boring machine; (ii) open-face shield excavation; and (iii) sequential construction using the New Austrian Tunneling Method (NATM). The measured data were obtained from three projects in London each involving different tunnel size and depth, but all excavated through deep units of stiff London clay. The measured performance in each case is evaluated using analytical solutions, that assume linear elastic properties for an elastic half-space, and numerical simulations that use an effective stress soil model, MIT-S1, with input parameters calibrated to elemental behavior of the London Clay. Although the numerical analyses achieve better agreement with the measured data, the analytical solutions perform well and could be used in future studies. The results indicate that the closed-face tunneling provided the best control of volume loss, while open-face shield excavation caused the largest ovalization of the tunnel cavity. The proposed methodology offers a practical framework for cataloging and comparing tunnel performance in future projects.